2017
DOI: 10.12944/crnfsj.5.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Physical Attributes and Modelling of Trans- Himalayan Seabuckthorn Berries

Abstract: Seabuckthorn is a highly perishable fruit found in trans-Himalayan region and North-Eastern part of India. It has enormous nutritional and medicinal properties. Physical attributes of fruits play an important role in the design of machines to meet various harvest and post harvest operations. In the present study properties like dimensions, true density, bulk density, sphericity, porosity and angle of repose were measured and correlated with the mass of the fruit. In addition linear, polynomial, quadratic, loga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The resulting pulse profile shown in Fig. 22 can be compared with other observations (Li et al 2016;Jaiswal & Naik 2017). Thus, it is clear that even with a low count rate it is possible to study pulsations.…”
Section: Pulsationmentioning
confidence: 60%
“…The resulting pulse profile shown in Fig. 22 can be compared with other observations (Li et al 2016;Jaiswal & Naik 2017). Thus, it is clear that even with a low count rate it is possible to study pulsations.…”
Section: Pulsationmentioning
confidence: 60%
“…Nevertheless, it was possible to estimate the spin period of 2.377441 ± 0.000016 s at the beginning of observation (MJD 58976.575405) and the spin-up rate of (3.9 ± 1.1) × 10 −11 Hz s −1 using LAXPC20 in single event mode and energy range of 3-20 keV. The resulting pulse profile shown in Figure 22 can be compared with other observations (Li et al 2016;Jaiswal & Naik 2017). Thus, it is clear that even with a low count rate it is possible to study pulsations.…”
Section: Pulsationmentioning
confidence: 81%
“…Yogurt or yoghourt is a food produced by bacterial fermentation of milk. Mwizerwa et al, 2 and Niamah 3 utilized cassava resistant starch and Saccharomyces boulardii had significantly quantity of yoghurt with acceptable sensory, and improved the physicochemical properties and microbial characteristics.Jaiswal et al, 4 proposed the measurement of physical properties may benefits as developing mechanical tool in design of sorting, grading, conveying, processing and packaging system.Leng et al, 5 , Plaitho et al, 6 and Manab et al, 7 suggested the heat treatments including stir-frying process, sterilization and microwave might effect on the qualities of foods and contents of nutrients and/or bioactive components, but relatively enhance the homogeneity and stability of products during storage period.Tinrat et al, 8 and Al-Manhel 9 also utilized food processing wastes and microbiall system by optimum conditions of extraction and fermentation to generate gelatin and exopoly saccharide which aspects as an alternative sourceinfood industry.…”
Section: Editorialmentioning
confidence: 99%